Changes of standard physiological-perceptual markers and circulating MicroRNAs in response to tennis match-play: A case report of two elite players - Hoppe, M. W.; Baumgart, C.; Hilberg, T.; Freiwald, J.; Wehmeier, U. F. (Journal of Human Kinetics, 2016)
This study aimed to describe the acute changes of both standard physiological-perceptual markers and circulating microRNAs in response to tennis match-play in a detailed case report. Two elite male baseliners with comparable tennis experience were tested for anthropometric and fitness related variables and played 2 h of match-play on a red-clay court. The changes of standard physiological-perceptual markers including the heart rate, lactate concertation, creatine kinase activity, urea concentration and rating of perceived exertion as well as circulating microRNA-133a, -486 and -126 expression rates were examined at 10 different time-points (i.e., pre, during and up to 24 h post match-play). Player 2 had lower fitness related variables, but a higher heart rate, lactate concentration, creatine kinase activity and rating of perceived exertion during play than player 1. Player 2 showed an increase in all microRNAs (=3.83-fold), most evident post match-play, whereas player 1 demonstrated a decrease (=0.41-fold). The time-course in the changes of all standard physiological-perceptual markers was similar in both players, whereas this of the microRNAs was different. It was concluded that the relative changes of the circulating microRNA-133a, -486 and 126 expression rates of both players differed in response to tennis match-play with respect to the experienced physiological-perceptual stress and the underlying fitness level. Therefore, circulating microRNAs can serve as additional biomarkers for tennis exercise physiology and may be assessed together with standard markers to conclude whether key cellular regulatory processes were induced in response to match-play.